Electrochemical nanoprobes for the chemical detection of neurotransmitters - Shen, Mei (Anal Methods, 2015)
Neurotransmitters, acting as chemical messengers, play an important role in neurotransmission, which governs many functional aspects of nervous system activity. Electrochemical probes have proven a very useful technique to study neurotransmission, especially to quantify and qualify neurotransmitters. With the emerging interests in probing neurotransmission at the level of single cells, single vesicles, as well as single synapses, probes that enable detection of neurotransmitters at the nanometer scale become vitally important. Electrochemical nanoprobes have been successfully employed in nanometer spatial resolution imaging of single nanopores of Si membrane and single Au nanoparticles, providing both topographical and chemical information, thus holding great promise for nanometer spatial study of neurotransmission. Here we present the current state of electrochemical nanoprobes for chemical detection of neurotransmitters, focusing on two types of nanoelectrodes, i.e. carbon nanoelectrode and nano-ITIES pipet electrode.